2019
DOI: 10.7554/elife.47434
|View full text |Cite
|
Sign up to set email alerts
|

The readily-releasable pool dynamically regulates multivesicular release

Abstract: The number of neurotransmitter-filled vesicles released into the synaptic cleft with each action potential dictates the reliability of synaptic transmission. Variability of this fundamental property provides diversity of synaptic function across brain regions, but the source of this variability is unclear. The prevailing view is that release of a single (univesicular release, UVR) or multiple vesicles (multivesicular release, MVR) reflects variability in vesicle release probability, a notion that is well-suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 94 publications
7
36
1
Order By: Relevance
“…Mitochondria boost local ATP generation and control Ca +2 levels which allow enhanced mobilization and recycling of synaptic vesicles for exocytosis, neurotransmitter release and for the generation of synaptic membrane potentials, specially under repetitive high-frequency firing 33 . Likewise, the presence of large vesicle pools and extensive and complex PSDs is associated with higher neurotransmitter release probabilities and synaptic efficacy 17, 18, 19, 35 and to the number and distribution of postsynaptic receptors 20, 22, 23 . The striking differences in these parameters between Po MC-L3/4 and S1-L5a boutons thus imply that the first may readily keep a high release probability at high-frequency firing rates, which is consistent with the observed capacity of MC Po synapses to transmit signals with higher efficacy and temporal acuity than Po S1 synapses 3, 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria boost local ATP generation and control Ca +2 levels which allow enhanced mobilization and recycling of synaptic vesicles for exocytosis, neurotransmitter release and for the generation of synaptic membrane potentials, specially under repetitive high-frequency firing 33 . Likewise, the presence of large vesicle pools and extensive and complex PSDs is associated with higher neurotransmitter release probabilities and synaptic efficacy 17, 18, 19, 35 and to the number and distribution of postsynaptic receptors 20, 22, 23 . The striking differences in these parameters between Po MC-L3/4 and S1-L5a boutons thus imply that the first may readily keep a high release probability at high-frequency firing rates, which is consistent with the observed capacity of MC Po synapses to transmit signals with higher efficacy and temporal acuity than Po S1 synapses 3, 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the RRPs are by 3-5-fold, the RPs by 2-fold and the resting pools by 2-fold larger than in rodent and non-human primate neocortex. It has been recently shown that the size of the RRP dynamically regulates multivesicular release in mice (Vaden et al 2019). Thus these large pools suggest reliable synaptic transmission even at high-frequency stimulation; hence a rapid depletion of the RRP and RP could be prevented by replenishment of synaptic vesicles from a large resting pool.…”
Section: Fig 3: Innervation Pattern Of Synaptic Boutons In Differentmentioning
confidence: 98%
“…In addition, the size and time course of action potential evoked Ca 2+ influx Sakmann 1996, 1998;Bischofberger and Jonas 2002), the occupancy of the putative Ca 2+ sensor driving vesicle fusion (Bollmann et al 2000;Schneggenburger and Neher 2000), the equilibration of intracellular Ca 2+ with the endogenous Ca 2+ buffer, and the eventual Ca 2+ -clearance (Helmchen et al 1997) can be accurately measured. Furthermore, the latency, size and time course of evoked quantal and multiquantal EPSCs (Borst and Sakmann 1996;Silver et al 2003;Molnar et al 2016;Holderith et al 2016;Seeman et al 2018;Rollenhagen et al 2018;Vaden et al 2019; reviewed by Neher 2015; Chamberland and Toth 2016) can be determined. However, there are still steps in the signal cascades that at present can only be simulated (Yamada and Zucker 1992;Bertram et al 1999;Meinrenken et al 2002Meinrenken et al , 2003Freche et al 2011).…”
Section: Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, at hMFBs, an increase in docked vesicles has been proposed as a mechanism for post-tetanic-potentiation (Vandael et al, 2020). At cerebellar parallel and climbing fiber synapses, PKA and its vesicle associated target, synapsin, dynamically control release site occupancy and dictate the number of vesicles released per action potential without altering P r (Vaden et al, 2019). Moreover, activation of silent synapses and/or addition of release sites have been suggested as potential mechanisms for the expression of presynaptic LTP at hMFBs (Tong et al, 1996;Emptage et al, 2003).…”
Section: Introductionmentioning
confidence: 99%